PENGARUH GOOD CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Aldaniar, Nadya; Sapari, Sapari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This research aimed to examine the effect of Good Corporate governance (GCG) and financial distress on the tax avoidance of companies listed on the Indonesia Stock Exchange (IDX). The GCG was measured by the number of independent commissioners divided by the number of commissioner boards, the number of institutional owners divided by the number of distributed stocks, and the audit committee. While financial distress was measured by Interest Coverage Ratio (ICR) and tax avoidance was measured by Cash Effective Tax Rate (CETR).The research was quantitative. Moreover, the population was Property and Real estate companies listed on IDX during 2019-2021. The data collection technique used purposive sampling. In line with that, there were 54 samples from 18 Property and Real estate companies.However, there were 12 outlier data. In total, there were 42 data samples obtained. Furthermore, the data analysis technique used multiple linear regression with SPSS. The result concluded that the audit committee had a positive effect on tax avoidance. In contrast, institutional ownership had a negative effect on tax avoidance.On the contrary, both independent commissioners and financial distress did not affect tax avoidance.